Benny & Joon - Arnold, Susan; Roth, Donna Arkoff; Berman, Barry, 1957-; Chechik, Jeremiah; Depp, Johnny; Masterson, Mary Stuart, 1966-; Quinn, Aidan; Moore, Julianne; Platt, Oliver; Pounder, C. C. H.; Hedaya, Dan.; Grifasi, Joe.; et al. (Santa Monica, Calif. : MGM Home Entertainment, 2001)
A mentally ill young woman who lives with her older brother finds her love in an eccentric young man who models himself after Buster Keaton.
Originally produced as a motion picture in 1993.
Special features: audio commentary; deleted scenes; costume make-up test and stunt reel; music video; theatrical trailer.
Director of photography, John Schwartzman ; editor, Carol Littleton ; music, Rachel Portman; production designer, Neil Spisak.
Johnny Depp, Mary Stuart Masterson, Aidan Quinn, Julianne Moore, Oliver Platt, C.C.H. Pounder, Dan Hedaya, Joe Grifasi, William H. Macy.
MPAA rating: PG.
DVD, 16.9 widescreen presentation (1.85:1); Dolby digital stereo or mono.
Keywords: Mental illness -- Drama; Interpersonal relations -- Drama; Mentally ill -- Family relationships -- Drama; Enfermedades mentales -- Teatro; Comedy films; Feature films; Video recordings for hard of hearing people